The Effect of Training and Compensation on Employee Performance at Crowne Plaza Hotel Bandung - Muhammad Farhan Zharfan; Ivan Gumilar Sambas Putra Putra (Enrichment : Journal of Management, 2022)
The tourism sector is one sector that supports the economy in Indonesia. The city of Bandung is one of the tourist destinations that is often visited by both local and foreign tourists, the tourism sector that is a necessity for tourists is the hotel sector, such as the Crowne Plaza Bandung hotel which is widely used by both local and foreign tourists. This study itself aims to determine how the partial effect of training and compensation on employee performance at the Crowne Plaza Bandung hotel. The method used in this study is descriptive and verification method with the population taken in this study is 120 employees from all existing divisions, and with a sample of 86 employees from all divisions using a questionnaire in the form of Google Forms. While the analytical method used in this study is multiple linear regression analysis at a significance level of 5%, F-test, coefficient of determination, and hypothesis testing with T-test. The data processing program used in this research is the Statistical Package for Social Sciences (SPSS) Ver.24.00. The results showed that training and compensation had an influence on employee performance at the Hotel Crowne Plaza Bandung and contributed 77.3%.